Laparoscopy in management of surgical causes of acute verses chronic pain abdomen in adults visiting tertiary care hospital in Telangana, India - Srinivas, Talla; Sreenivas, Sudagani; Anusha, Doddoju Veera Bhadreshwara (International Surgery Journal, 2021)
Background: Pain abdomen accounts for about 14.2% of all emergency hospitalization. Many patients remain undiagnosed even after excluding the common disorders by meticulous investigations. In case of diagnostic uncertainty, laparoscopy may help to avoid unnecessary laparotomy, provide accurate diagnosis. The current study aimed at comparing the role of laparoscopy in management of surgical causes of acute and chronic pain abdomen. Methods: A prospective study was done in 168 adult patients attending tertiary care hospital, selected by convenience sampling method. After clinical examination and relevant investigation, patients in need of diagnostic and therapeutic laparoscopic management were included in study. Laparoscopic findings and postoperative status of patients, with acute and chronic pain abdomen were compared with relevant statistical tests. Results: Mean age of patients was 35.8 years. Majority of the patients were females (58.3%). 41.1% and 58.9% patients had acute and chronic pain abdomen, respectively. Though more patients with chronic pain abdomen (58.9%) underwent laparoscopy when compared with acute pain abdomen (41.1%) it was not statistically significant, also post-operative status though found to be better in patients with chronic pain abdomen was not statistically significant. Conclusions: Though prevalence of laparoscopic intervention and better outcome was found more in patients with chronic abdominal pain in the present study it was not statistically significant.